2009
DOI: 10.1016/j.cbpa.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of brain nitric oxide in the thermoregulation of broiler chicks

Abstract: Nitric oxide (NO) plays a key role in body temperature (Tb) regulation of mammals, acting on the brain to stimulate heat loss. Regarding birds, the putative participation of NO in the maintenance of Tb in thermoneutrality or during heat stress and the site of its action (periphery or brain) is unknown. Thus, we tested if NO participates in the maintenance of chicks' Tb in those conditions. We investigated the effect of intramuscular (im; 25, 50, 100mg/kg) or intracerebroventricular (icv; 22.5, 45, 90, 180 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Similar report by Kim et al (80) showed that citrulline ingestion improved NO synthesis rate. Also, N G -nitro-L-arginine methyl ester (L-NAME), a nonselective NOS inhibitor, when administered to chicks was able to inhibit heat stress induced hyperthermia, however, the plasma levels of Nitrite/ Nitrate levels were unaffected (22). This findings differ from Chowdhury et al (45) who reported that oral injections of L-Cit did not significantly increase plasma NOx concentrations both under ambient temperatures or heat stressed conditions.…”
Section: Plasma Metabolites and Circulating No Levelsmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar report by Kim et al (80) showed that citrulline ingestion improved NO synthesis rate. Also, N G -nitro-L-arginine methyl ester (L-NAME), a nonselective NOS inhibitor, when administered to chicks was able to inhibit heat stress induced hyperthermia, however, the plasma levels of Nitrite/ Nitrate levels were unaffected (22). This findings differ from Chowdhury et al (45) who reported that oral injections of L-Cit did not significantly increase plasma NOx concentrations both under ambient temperatures or heat stressed conditions.…”
Section: Plasma Metabolites and Circulating No Levelsmentioning
confidence: 77%
“…During thermal stress, NO as an endothelial vasodilator (21) acts to stimulate peripheral blood flow, thereby increasing autonomic heat dissipation. Likewise in chicks, NO has been shown to act via the central nervous system (CNS) to regulate body temperature (22). Most biological functions of NO are mediated via the activities of the NO synthase (NOS), which includes, endothelial NOS (eNOS), neuronal NOS (nNOS) and the inducible NOS (iNOS) isoform (23).…”
Section: Introductionmentioning
confidence: 99%
“…But in birds also under these conditions the role of NO seems to be different from that observed in mammals. In 5-days-old chicks under thermoneutral and heat stress conditions intramuscular as well as intracerebroventricular injections of NOS inhibitor L-NAME decreased body temperature and thus inhibited heat stress-induced hyperthermia [16]. …”
Section: Discussionmentioning
confidence: 99%
“…In mammals and birds, during different developmental periods, NO plays a crucial role in regulation of various physiological functions, which are mediated by the hypothalamus, like thermoregulation [1216], water balance [17, 18] and fever [19, 20], feeding behaviour [2125], energy balance [26], and cardiovascular regulation [2729]. However, in birds under thermoneutral conditions or heat load, for instance, the thermoregulatory effect of NO seems to be different from that in mammals [16], in which central NO mostly induces heat loss responses and finally decreases body temperature [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation